Fatty acid alterations and polymyxin B binding by lipopolysaccharides from Pseudomonas aeruginosa adapted to polymyxin B resistance. - Conrad, R S (1989)
Lipopolysaccharides were extracted from freeze-dried cells of Pseudomonas aeruginosa PAO1 (polymyxin B susceptible), isolate A (polymyxin B resistant), and isolate A-reverted (polymyxin B intermediate resistance) by either the phenol-chloroform-petroleum ether or the modified phenol-water method. Isolate A and isolate A-reverted had drastic losses of 2-hydroxydodecanoic acid and significant decreases in 3-hydroxydecanoic acid. Concentrations of amide-linked 3-hydroxydecanoic acid were similar in all three strains. Minor alterations were noted in the composition of 3-deoxy-D-manno-2-octulosonic acid, heptose, phosphate, neutral sugars, and amino compounds. The concentrations of rhamnose in isolate A and of rhamnose and glucose in isolate A-reverted were significantly different from those in PAO1. Trace amounts of mannose and other minor unidentified carbohydrates were detected in all strains. Polymyxin B included in isolate. A growth medium complexed with lipopolysaccharides and remained bound throughout purification. PAO1 lipopolysaccharides bound more polymyxin B than did isolate A lipopolysaccharides. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis indicated minor differences in smooth- and rough-form lipopolysaccharides of the different strains. We propose that loss of hydroxy fatty acids from lipopolysaccharides perturbs outer membrane hydrophobicity and is a contributing factor to polymyxin B adaptive resistance.